COMPREHENSIBLE INPUT, EXPLICIT TEACHING, AND CORRECTIVE FEEDBACK IN GENRE BASED APPROACH TO TEACHING SPOKEN HORTATORY EXPOSITION - Fajriah, Yustika Nur (2015)
This study aims to investigate the effectiveness of comprehesible input, explicit teaching and corrective feedback in teaching spoken hortatory exposition. This study relies on a case study design involving classroom observations, students' texts documentation, and dependent t-test as strategies of data collection. The data from observations were analyzed by using four stages of analysis: organizing, transcribing, converting, classifying, describing, and interpreting. The students' texts were analyzed by using SOLOM; that is, Students Oral Language Observation Matrix, and the rubric adapted from Butt, Fahey, Feez, spinks, and Yallop (2000) and Emilia (2011). The analysis shows that comprehensible input, explicit teaching and corrective feedback develop students' skills in spoken hortatory exposition. Students were able to improve their ability in the general aspects of speaking including comprehension, fluency, grammar, and pronunciation. In addition, they were able to speak by following the genre moves of hortatory exposition. This study suggests that the techniques of comprehensible input, explicit teaching, and corrective feedback are recommended to be applied in a language teaching process. Keywords: Comprehensible Input, Explicit Teaching, Corrective Feedback